Environmental Friendliness in Low Carbon Supply Chain and Operations - Muhammad Shabir, Shaharudin; Fernando, Yudi (IGI Global, 2021)
Managing operations in manufacturing industry has progressed significantly over the years due to customer requirements. Globalization and environmental awareness have force firm’s operations to align with the direction of environmental management. The importance of carbon emission reduction for environmental management has led firms to adopt low carbon operations practices such as energy management. The emergence of energy management and environmental friendliness principle in business operations have changed the landscape of business competition in the manufacturing industry. Nevertheless, the outcomes and concept remain unclear and availability of limited studies on the specific scope of environmental friendliness have not extensively discussed. As such, the purpose of this chapter is to discuss the environmental friendliness approach in operations from the perspective of manufacturing industry.